Physical, Textural and Sensory Properties of Cookies Incorporated with Grape Skin and Seed Preparations - Kuchtová Veronika; Kohajdová Zlatica; Karovičová Jolana; Lauková Michaela (Polish Journal of Food and Nutrition Sciences)
This study is oriented to the effect of the incorporation of grape skins and grape seeds (0, 5, 10, and 15% to weight of flour) obtained from a red grape on the rheological properties of wheat dough, and on qualitative parameters and sensory properties of the prepared cookies.